Comparison of angiographic change in side-branch ostium after drug-coated balloon vs. drug-eluting stent vs. medication for the treatment of de novo coronary bifurcation lesions - Ae-Young Her; Bitna Kim; Sunwon Kim; Yong Hoon Kim; Bruno Scheller; Eun-Seok Shin (European Journal of Medical Research, 2024)
Abstract Objectives Data on side-branch (SB) ostial effect after drug-coated balloon (DCB) treatment in the context of de novo coronary bifurcation lesions are limited. We aimed to investigate the angiographic outcomes of SB ostium after DCB treatment compared with drug-eluting stents (DESs) implantation in the main vessel (MV) or optimal medical therapy (OMT) for the treatment of de novo coronary bifurcation lesions. Methods Serial angiographic changes in the SB ostium were compared between DCB, DES, and medication alone for MV treatment. Δ value was calculated by subtracting the follow-up value from the pre-procedure value. Results A total of 132 bifurcation lesions were included for analysis (44 lesions in DCB group; 38 lesions in DES group; 50 lesions in OMT group). The minimal lumen diameter (MLD) of SB ostium showed an increase at follow-up in the DCB group, whereas a decrease was observed in both the DES and OMT groups (ΔMLD: −0.16 ± 0.45 mm for DCB group vs. 0.50 ± 0.52 mm for DES group vs. 0.08 ± 0.38 mm for OMT group, p < 0.001). The diameter stenosis (DS) of SB ostium showed a marked decrease at follow-up in the DCB group, in contrast to an increase observed in both the DES and OMT groups (ΔDS: 8.01 ± 18.96% for DCB group vs. −18.68 ± 18.60% for DES group vs. −2.05 ± 14.58% for OMT group, p < 0.001). Conclusions In de novo coronary bifurcation lesions, DCB treatment on the MV demonstrated favorable angiographic outcomes in the SB ostium at 6–9 month follow-up compared to DES implantation or OMT.